Simplifying
4x + 2(x + 6) = 36
Reorder the terms:
4x + 2(6 + x) = 36
4x + (6 * 2 + x * 2) = 36
4x + (12 + 2x) = 36
Reorder the terms:
12 + 4x + 2x = 36
Combine like terms: 4x + 2x = 6x
12 + 6x = 36
Solving
12 + 6x = 36
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-12' to each side of the equation.
12 + -12 + 6x = 36 + -12
Combine like terms: 12 + -12 = 0
0 + 6x = 36 + -12
6x = 36 + -12
Combine like terms: 36 + -12 = 24
6x = 24
Divide each side by '6'.
x = 4
Simplifying
x = 4